Fermentation in the Small Intestine Contributes Substantially to Intestinal Starch Disappearance in Calves. Issue 6 (15th April 2015) - Gilbert, Myrthe S; Pantophlet, André J; Berends, Harma; Pluschke, Anton M; van den Borne, Joost JGC; Hendriks, Wouter H; Schols, Henk A; Gerrits, Walter JJ
Abstract: Background: The proportion of starch disappearing from the small intestinal lumen is generally lower in ruminants than in monogastric animals, and there are indications that the starch digestion capacity in ruminants is limited. Objectives: Milk-fed calves were used to study the rate-limiting enzyme in starch hydrolysis and to quantify starch fermentation in ruminants. Methods: Forty male Holstein-Friesian calves were fed milk replacer containing either lactose (control) or 1 of 4 corn starch products. The following starch products differed in the enzyme ratios required for their complete hydrolysis to glucose: gelatinized starch [α-amylase and (iso)maltase], maltodextrin [(iso)maltase and α-amylase], maltodextrin with α-1, 6-branching (isomaltase, maltase, and α-amylase), and maltose (maltase). In the adaptation period, calves were stepwise exposed to an increasing dose of the starch product for 14 wk to allow maximal adaptation of all enzyme systems involved. In the experimental period, apparent total tract and ileal starch product disappearance, total tract starch product fermentation, and α-amylase, maltase, and isomaltase activities were determined at 18% inclusion of the starch product. Results: Maltase and isomaltase activities in the brush border did not increase for any of the starch product treatments. Luminal α-amylase activity was lower in the proximal (3.9 ± 3.2 and 2.7 ± 1.7 U/mg Co for control and starch product calves, respectively) but greater in the distal small intestine of starch-fed calves than in control calves (0.0 ± 0.0 and 6.4 ± 1.5 U/mg Co for control and starch product calves, respectively; means ± SEs for control and means ± pooled SEMs for starch product treatments). Apparent ileal (61.6% ± 6.3%) and total tract (99.1% ± 0.4%) starch product disappearance did not differ between starch product treatments, suggesting that maltase activity limits starch digestion in ruminants. Total tract starch product fermentation averaged 414 ± 43 g/d, corresponding to 89% of intake, of which half was fermented before the terminal ileum, regardless of starch product treatment. Conclusion: Fermentation, rather than enzymatic digestion, is the main reason for small intestinal starch disappearance in milk-fed calves.